2012
DOI: 10.5194/amt-5-123-2012
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic ozone hole as observed by IASI/MetOp for 2008–2010

Abstract: Abstract. In this paper we present a study of the ozone hole as observed by the Infrared Atmospheric Sounding Interferometer (IASI) on-board the MetOp-A European satellite platform from the beginning of data dissemination, August 2008, to the end of December 2010.Here we demonstrate IASI's ability to capture the seasonal characteristics of the ozone hole, in particular during polar night. We compare IASI ozone total columns and vertical profiles with those of the Global Ozone Monitoring Experiment 2 (GOME-2, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…In the lower stratosphere, this bias confirms the bias estimated by previous works (e.g. Scannell et al, 2012) and in other regions such as Iberian Peninsula (Anton et al, 2011), at midlatitudes and in the tropics . Dufour et al (2012) showed that three independent IASI ozone retrieval codes tend to overestimate ozone in the upper troposphere/lower stratosphere region in the midlatitudes and the tropics.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the lower stratosphere, this bias confirms the bias estimated by previous works (e.g. Scannell et al, 2012) and in other regions such as Iberian Peninsula (Anton et al, 2011), at midlatitudes and in the tropics . Dufour et al (2012) showed that three independent IASI ozone retrieval codes tend to overestimate ozone in the upper troposphere/lower stratosphere region in the midlatitudes and the tropics.…”
Section: Resultssupporting
confidence: 90%
“…Applications range from the study and the monitoring of the stratospheric ozone hole to tropospheric chemistry and air quality (e.g. Scannell et al, 2012;Parrington et al, 2012;Wespes et al, 2012). Ozone retrievals are performed in the 1025-1075 cm −1 spectral range, in order to minimize the computation time and avoid interferences with water vapour lines.…”
Section: Satellite Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ozone profiles are retrieved in near-real time, using the FORLI-O3 (Fast Optimal Retrievals on Layers for IASI) software , and will be available as part of the IASI Level 2 product processing facility (August et al, 2012, Table 1a-c). Validation was performed using ground-based (Antón et al, 2011;Dufour et al, 2012), aircraft (Parrington et al, 2012;Pommier et al, 2012), balloon (Gazeaux et al, 2013) and other satellite data (Scannell et al, 2012).…”
Section: Iasimentioning
confidence: 99%
“…Validation with and comparison to independent measurements of other IASI products have been performed Keim et al, 2009;Pittman et al, 2009;Viatte et al, 2011;Dufour et al, 2012;Pommier et al, 2012;Scannell et al, 2012;Gazeaux et al, 2013) and also comparison to models (Parrington et al, 2012). In general, these studies focus on the determination of the bias and the correlation with respect to independent measurements and on the determination of the information content.…”
Section: Existing Iasi Ozone Data Productsmentioning
confidence: 99%